A selective, tracking, and power adaptive far-field wireless power transfer system - Belo, Daniel (2019)
This paper proposes a selective, tracking, and power adaptive far-field wireless power transfer (WPT) system that may be integrated into passive wireless sensor networks (PWSNs). Both transmitter and receiving nodes are developed with features that allow them to cooperate. The system operates based on a backscattered pilot signal, which is used to control and focus the radiated energy. The transmitter may change between several states by turning on or off sets of antenna elements. Each of these states will transmit and consume a specific amount of power, and they will be selected based on the node's received signal strength (RSS). The receiving nodes are low complexity and battery-less devices, which use a small portion of the rectified energy to create an RSS-dependent modulation frequency, used to drive a backscatter modulator. Based on the nonlinear response of the rectifying devices, additional hardware was integrated into the nodes to activate/wake up them from specific wireless power signals. A complete system operating at 5.8 GHz for WPT and 3.6 GHz for the pilot signal is reported. It will be shown that effective far-field WPT links can be created with reasonable simplicity.